Metode Diskusi dalam Mata Pelajaran Fiqih sebagai Bentuk Peningkatan Hasil Belajar Siswa - Zuhdiana Fauziyah (La-Tahzan: Jurnal Pendidikan Islam, 2022)
Education is a process in order to foster students so that they can adjust to their environment and will cause changes in students towards a better direction in community life. These changes occur through the process of teaching and training. In learning, teachers use learning strategies, one of which uses the discussion method. SMP Muhammadiyah Margasari Margasari District Tegal Regency applied the discussion method in fiqh subjects, especially in class VIII. This research is a field research with a qualitative approach. Data collection techniques using observation, interviews, and documentation. The data analysis used qualitative descriptive analysis with 5W + 1H guidelines with the SWOT formula (Strength, Weakness, Opportunity, Threat). The results showed that the application of the discussion method in fiqh subjects went through three stages, namely planning, implementation, and closing. The application of the discussion method runs well smoothly, where students are active in learning, have the skills to ask and answer and the results achieved show that student scores have increased after the application of the discussion method.